ENDOPHRAGMIELLA BOGORIENSIS RIFAI, SPEC. NOV. (HYPHOMYCETES) - Mien A. Rifai (BRIN Publishing (Penerbit BRIN), 2008)
RIFAI, M.A. 2008. Endophragmiella bogoriensis Rifai, spec. nov. (Hyphomycetes). Reinwardtia 12 (4): 275 – 276.–– A new species of Endophragmiella is described and illustrated based on a specimen found growing on dead branchlets of Morinda citrifolia in Bogor, West Java, and compared with its closely related congeners thus far known.